Mutacin 1140 Lantibiotic Variants Are Efficacious Against Clostridium difficile Infection - Kers, Johan A.; Sharp, Robert E.; Defusco, Anthony W.; Park, Jae H.; Xu, Jin; Pulse, Mark E.; Weiss, William J.; Handfield, Martin (Frontiers in Microbiology, 2018)
Lantibiotics offer an untapped pipeline for the development of novel antibiotics to treat serious Gram-positive (+) infections including C. difficile. Mutacin 1140 (MU1140) is a lantibiotic produced by Streptotoccus mutans and acts via a novel mechanism of action, which may limit the development of resistance. This study sought to identify a lead compound for the treatment of C. difficile associated diarrhea (CDAD). Compounds were selected from a saturation mutagenesis library of 418 single amino acid variants of MU1140. Compounds were produced by small scale fermentation, purified, characterized and then subjected to a panel of assays aimed at identifying the best performers. The screening assays included: in vitro susceptibility testing (MIC against M. luteus, C. difficile, vancomycin-resistant Enterococci (VRE), Staphylococcus aureus, Streptococcus pneumonia, Mycobacterium phlei and Pseudomonas aeruginosa; cytotoxicity screening on HepG2 hepatocytes; in vitro pharmacological profiling with the Safety Screen 44TM, metabolic and chemical stability in biologically-relevant fluids (FaSSGF, FaSSIF and serum); and efficacy in vivo. Several lantibiotic compounds had better MIC against C. difficile, compared to vancomycin, but not against other bacterial species tested. The Safety Screen 44TM in vitro pharmacological profiling assay suggested that this class of compounds has relatively low overall toxicity and that compound OG253 (MU1140, Phe1Ile) is not likely to present inadvertent off-target effects, as evidenced by a low promiscuity score. The in vitro cytotoxicity assay also indicated that this class of compounds was characterized by low toxicity; the EC50 of OG253 was 636 mg/mL on HepG2 cells. The half-life in simulated gastric fluid was >240 min. for all compound tested. The stability in simulated intestinal fluid ranged between a half-life of 5 min to >240 min, and paralleled the half-life in serum. OG253 ultimately emerged as the lead compound based on superior in vivo efficacy along with an apparent lack of relapse in a hamster model of infection. The lessons learned from this report are applicable to therapeutic lanthipeptides in general and may assist in the design of novel molecules with improved pharmacological, therapeutic and physicochemical profiles. The data presented also support the continued clinical development of OG253 as a novel antibiotic against CDAD